Anti-inflammatory, analgesic and in vivo-in vitro wound healing potential of the Phlomis rigida Labill. extract. (10th February 2021) - Okur, Mehmet Evren; Karadağ, Ayşe Esra; Özhan, Yağmur; Sipahi, Hande; Ayla, Şule; Daylan, Benay; Kültür, Şükran; Demirci, Betül; Demirci, Fatih
Abstract: Ethnopharmacological relevance: The preparations of Phlomis aerial parts are used traditionally in Anatolia for wound healing and in inflammatory disorders. Methods: For the identification of the active fraction, the air dried aerial parts of Phlomis rigida Labill. were extracted by methanol and fractionated successively by n -hexane, dichloromethane and ethyl acetate, respectively. The phenolic constituents were characterized by the Folin-Ciocaltheu method; the antioxidant activity was performed by ABTS and DPPH radical scavenging assays. In vitro anti-inflammatory activity was evaluated by LOX enzyme inhibition, spectrophotometrically as well as cell cultures. The wound healing properties of P. rigida extract gels were studied via in vitro cell culture methods and in vivo by excisional wound model using Balb-c mice. The P. rigida extract was analyzed and characterized by GC-FID, GC-MS, and LC-MS. Results: The P. rigida methanol extract showed moderate LOX inhibitory at IC50 = 19.5 ± 2.8 μ g/mL whereas the antioxidant activity was by DPPH IC50 = 0.89 mg/mL, and by ABTS IC50 = 0.99 mg/mL, respectively. In addition, a remarkable P. rigida extracts anti-inflammatory activity was observed in the cell culture assay, which was then confirmed by the in vitro wound healing activity applied at 0.125–0.5 mg/mL concentrations, resulting in a dose-dependent increase in wound closure at the final stage. The P. rigida gel formulation was prepared to evaluate the extract in vivo, whereas the experimental results of the new gel formulation supported the findings of the in vitro wound healing activity. Conclusion: The findings of this in vitro and in vivo study suggest that the wound healing and anti-inflammatory properties provide a scientific evidence of the ethnopharmacological application of Phlomis species. Graphical abstract: Image 1 Highlights: Bioactive Phlomis rigida Labill. extracts were prepared. In vitro antioxidant, antimicrobial, anti-inflammatory and analgesic activities were evaluated. In vivo and in vitro wound healing properties were observed. Luteolin and apigenine were identified by LC-MS. Hexadecanoic acid (32%), neophytadiene isomer (16.8%), and myrcene (11.6%) were the major volatiles identified by GC/MS.